Clinical superiority of an innovative two-component compression system versus four-component compression system in treatment of active venous leg ulcers: A randomized trial. (October 2019) - Gillet, Jean L; Guex, Jean J; Allaert, François A; Avouac, Bernard; Leger, Philippe; Blaise, Sophie; Marchand, Angélique; Maillard, Hervé; Simon, Magali; Amor, Cyrine B; Pasqualini, Marion
Objective: To evaluate the efficacy, safety and acceptability of an innovative two-component versus a well-established four-component compression systems in the management of venous leg ulcer. Method: Multicentre randomized controlled trial in patients with active venous leg ulcer. Patients were followed-up monthly for a maximum of 16 weeks. The primary endpoint was the complete healing rate at 16 weeks. Results: Ninety-two patients were randomized to either the two-component BIFLEX® Kit group ( n = 49) or the four-component PROFORE® group ( n = 43). In the full analysis set ( n = 88), a complete healing rate of 48.9% and 24.4% was reported in BIFLEX® Kit versus PROFORE® groups, respectively (i.e. a superiority of 24.5%, p = 0.02). Acceptability of BIFLEX® Kit was higher from both the patients' and physicians' perspectives. Conclusion: The BIFLEX® Kit represents a valid alternative therapy in the management of venous leg ulcer according to its clinical efficacy, safety and acceptability with potential positive impacts on healthcare costs.